Ethnomathematics of Apem Cake: Integrating Local Culture into Junior High School Mathematics Learning - Uday, Muhammad Ali; Handayani, Ucik Fitri (Noumerico: Journal of Technology in Mathematics Education, 2025)
Learning mathematics at the junior high school level is often considered difficult and uninteresting because the material rarely relates to everyday life. This study explores the concept of ethnomathematics in traditional apem cakes as a source of contextualised teaching materials in mathematics. A descriptive, qualitative method was employed, utilizing observation, documentation, and interviews with two informants who were knowledgeable about the history and preparation of apem cakes to collect data. The results showed that apem cakes have geometric shapes, such as circles and cones, which can be used to teach geometric concepts, including area, circumference, and volume, as well as calculations and ingredient comparisons. Additionally, the cultural significance of apem cakes can enrich the learning experience and boost student engagement. The study concludes that apem cakes have the potential to serve as a meaningful and contextual learning medium. Practically, teachers can design lesson plans utilising apem cake-based calculation examples to make learning more active and relevant for students. However, this study is limited to two informants and has not yet been tested in the classroom, so the results remain descriptive. Further research is recommended to develop student worksheets based on apem cakes and test their effectiveness with junior high school students.